ANALYSIS OF BUSINESS PERFORMANCE IN THE ECONOMY OF NAMANGAN REGION AND THE IMPLEMENTATION OF MANAGEMENT STRATEGIES IN THE FIELD (Journal of Pharmaceutical Negative Results, 2022)
Strategic planning is a process of carefully and thoughtfully aligning the strengths of a company’s business to the opportunities that are available to the company in its chosen business environment. Strategy includes processes of formulation and implementation; strategic planning helps coordinate both. However, strategic planning is analytical in nature (i.e., it involves "finding the dots"); strategy formation itself involves synthesis (i.e., "connecting the dots") strategic thinking. As such, strategic planning occurs around the strategy formation activity.